1998
DOI: 10.2135/cropsci1998.0011183x003800020097x
|View full text |Cite
|
Sign up to set email alerts
|

Registration of NC96BGTD1, NC96BGTD2, and NC96BGTD3 Wheat Germplasm Resistant to Powdery Mildew

Abstract: graminis Pers.:Pers.) and common root rot [caused primarily by Bipolaris sorokiniana (Sacc. in Sorok.) Shoem.]. The germplasm line has grain yield, days to maturity, test weight, kernel weight, grain protein content, and gluten strength similar to Neepawa and the recurrent parent BW90. P8913-V2A5 is heterogeneous for leaf rust reaction (caused by P. recondita Roberge ex Desmaz.) and, at an average height of 104 cm, is 5 cm shorter than Neepawa. HY358 and HY320, the recurrent parents of P8917-B4D4 and P8921-Q4C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…tauschii subsp. strangulata accession (Murphy et al 1998). Since Pm-M53 and Pm35 originated from different subspecies of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…tauschii subsp. strangulata accession (Murphy et al 1998). Since Pm-M53 and Pm35 originated from different subspecies of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pm10 and Pm15 are not effective against Bgt, they can be traced from A. tauschii (McIntosh et al, 1995). Four new germplasm lines, NC96BGTD1, NC96BGTD2, were released with wheat powdery mildew resistance alleles, which were transferred from A. tauschii and two germplasm line NC96BGTD3 and NC97BGTD7 contain Pm34 and Pm35 (Murphy et al, 1998;Mirinda et al, 2006Mirinda et al, , 2007. Shi et al, (1998) identified new allele(s) for powdery mildew resistance transferred from Ae.…”
Section: Sources and Distribution Of Resistance Genesmentioning
confidence: 99%
“…Tauschii ssp. Tauschii in NC92-8562 and NC109-2-1-G1-1; diploid einkorn wheat (T. monococcum) (2n=2x=14, AA genome) derivative common wheat germplasm NC96BGTA5 contain Pm25 Murphy et al, 1998).…”
Section: Sources and Distribution Of Resistance Genesmentioning
confidence: 99%
“…tauschii to wheat can be done either by direct hybridization or as synthetic hexaploid wheat ( McFadden and Sears, 1946 ; Gill and Raupp, 1987 ). Both of these approaches have been used to transfer resistance against pathogens ( Dhaliwal et al, 1991 ; Cox et al, 1994 ; Murphy et al, 1998 ; Singh et al, 2000 ), pests ( Gill et al, 1986a ; Xu et al, 2006 ), abiotic stresses ( Ryan et al, 2010 ; Pradhan et al, 2012 ; Ogbonnaya et al, 2013 ), for quality traits ( Lagudah et al, 1987 ; Cox et al, 1997 ; Brown-Guedira et al, 2005 ) as well as yield parameters ( Mujeeb-Kazi et al, 2008 ; Okamoto et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%